Association Between Chronic Pain, Coping Strategies, and Sleep Quality in Rural Chinese Older Adults: A Cross-Sectional Study - Tao X; Cheng C; Bai J (Clinical Interventions in Aging, 2025)
Xin Tao,1 Cheng Cheng,2 Jie Bai3 1Eye & ENT Hospital of Fudan University, Shanghai, People’s Republic of China; 2School of Nursing, Fudan University, Shanghai, People’s Republic of China; 3Shanghai First Maternity and Infant Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of ChinaCorrespondence: Jie Bai, Shanghai Key Laboratory of Maternal Fetal Medicine, Shanghai Institute of Maternal-Fetal Medicine and Gynecologic Oncology, Shanghai First Maternity and Infant Hospital, School of Medicine, Tongji University, Shanghai, Shanghai, 200092, People’s Republic of China, Tel +86 21 13865011018, Email baijieyfy@tongji.edu.cnPurpose: This study aimed to investigate the current status of sleep quality and explore the associations between chronic pain, sleep quality, and coping strategies in older adults living in rural areas of China, a topic of growing interest and importance in gerontology and public health.Patients and Methods: This was an observational, cross-sectional study with a convenience sample of Chinese older adults from a rural community in Northern Anhui, China, conducted from September to December 2023. A self-reported questionnaire was used to collect data on socio-demographic items, chronic pain (visual analogue scale, VAS), coping strategies (Coping Strategies Questionnaire-Revised, CSQ-R), and sleep quality (Athens Insomnia Scale, AIS). Descriptive statistics, Pearson correlation, Stepwise multiple linear regression, and mediation analysis were used to analyze the data.Results: A total of 158 participants (48.7% female) were included in the study. Most participants (73.4%, n = 116) reported poor sleep quality. The regression model revealed significant associations between sleep quality and chronic pain (Beta = 0.599, t = 9.99, p < 0.001) and praying as a way of coping (Beta = 0.165, t = 2.72, p = 0.007). The model explained 46.5% of the variance in sleep quality (p < 0.01). Mediation analysis indicated that chronic pain had an indirect effect on sleep quality via praying, even after controlling for covariates (B = 0.137, 95% CI = 0.0614, 0.2227).Conclusion: This study displayed a significant association between chronic pain, coping strategies, and sleep quality in Chinese older adults living in rural areas. Chronic pain directly affects sleep quality, while praying as a coping strategy may mitigate this effect. Nurses should prioritize pain management and promote adaptive coping strategies to improve sleep quality.Keywords: chronic pain, coping, older adults, sleep